Predict, Organize, Rehearse, Practice and Evaluate(PORPE) Method to Teach Students’ Reading Comprehension - Afrida Wulansari; Dwi Andriani; Eka Agustina (Channing : Journal of English Language Education and Literature, 2018)
The problem of this study is "is it effective using PORPE method to teach reading comprehension at the seventh-grade students of SMP Pangudi Luhur Santo Aloysius Sukaraja OKU Timur?". The objective of the study is "to find out whether or not PORPE method is effective to teach reading comprehension at the seventh grade of SMP Pangudi Luhur Santo Aloysius Sukaraja OKU Timur." In this study, the pre-experimental method was used. The population is all of the seventh-grade students of SMP Pangudi Luhur Santo Aloysius Sukaraja OKU Timur, with the total number of the students 30 students. The sample is 30 students taken through saturated sampling consisting of 30 students as the sample. Based on the description, it could be seen that the result of students pre-test the average score was 5.01 and the result of the student's average score in post-test was 8.01. The result calculation of the matched t-test was 5.45. the t-obtained was higher than t-table 1.699. It means that Ho was rejected and Ha was accepted. In another word, the result of the study showed that it was effective teaching reading comprehension by using PORPE method at the seventh-grade students of SMP Pangudi Luhur Santo Aloysius Sukaraja OKU Timur.